Detection and Measurement of Unhealthy, Environment-Derived Aerosol Materials in an Emergency Department. (October 2015) - Choi, Bryan Y.; Kobayashi, Leo; Pathania, Shivany; Miller, Courtney B.; Locke, Emma R.; Stearns, Branden C.; Hudepohl, Nathan J.; Patefield, Scott S.; Suner, Selim; Williams, Kenneth A.; Machan, Jason T.; Jay, Gregory D.
Objective: To measure unhealthy aerosol materials in an Emergency Department (ED) and identify their sources for mitigation efforts. Background: Based on pilot findings of elevated ED particulate matter (PM) levels, investigators hypothesized that unhealthy aerosol materials derive from exogenous (vehicular) sources at ambulance receiving entrances. Methods: The Aerosol Environmental Toxicity in Healthcare-related Exposure and Risk program was conducted as an observational study. Calibrated sensors monitored PM and toxic gases at Ambulance Triage Exterior (ATE), Ambulance Triage Desk (ATD), and control Public Triage Desk (PTD) on a 3/3/3-day cycle. Cassette sampling characterized PM; meteorological and ambulance traffic data were logged. Descriptive and multiple linear regression analyses assessed for interactions between aerosol material levels, location, temporal variables, ambulance activity, and meteorological factors. Results: Sensors acquired 93, 682 PM0.3, 90, 250 PM2.5, and 93, 768 PM5 measurements over 366 days to generate a data set representing at least 85.6% of planned measurements. PM0.3, PM2.5, and PM5 mean counts were lowest in PTD; 56%, 224%, and 223% higher in ATD; and 996%, 200%, and 63% higher in ATE, respectively (all p < .001). Qualitative analyses showed similar PM compositions in ATD and ATE. On multiple linear regression analysis, PM0.3 counts correlated primarily with location; PM2.5 and PM5 counts correlated most strongly with location and ambulance presence. PM < 2.5 and toxic gas concentrations at ATD and PTD patient care areas did not exceed hazard levels; PM0.3 counts did not have formal safety thresholds for comparison. Conclusions: Higher levels of PM were linked with ED ambulance areas, although their health impact is unclear.